Pembelajaran akhlak berbasis teknologi dan SDGs: penggunaan aplikasi Assemblr Education di Sekolah Indonesia Kuala Lumpur - Eva Kartina Rahmadhani; Ahmadi Ahmadi; Taufiqqurrahman Hasyim (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
This study examines the use of the Assemblr Edu application in teaching moral education at Sekolah Indonesia Kuala Lumpur (SIKL), Malaysia. Drawing on a qualitative case study approach, the research involved in-depth interviews with teachers and students, complemented by classroom observations to capture authentic learning practices. Findings indicate that the integration of Assemblr Edu significantly increased student engagement and facilitated a deeper understanding of moral concepts by presenting abstract values through interactive and contextually relevant digital content. The use of augmented reality features enabled students to connect moral principles to real-life situations, thus supporting character development in a more meaningful way. In line with the Sustainable Development Goals (SDGs), these outcomes particularly support SDG 4 (Quality Education) by promoting inclusive and effective learning through technology-enhanced pedagogy, and contribute to SDG 16 (Peace, Justice, and Strong Institutions) by strengthening ethical awareness, responsible citizenship, and values-based education. Despite these positive results, the study also identified several challenges, including limited access to technological resources and the need for systematic teacher training to ensure effective implementation. To address these issues, the study proposes practical recommendations focused on strengthening technological infrastructure and enhancing educators' digital competencies. Overall, the study highlights the potential of AI-powered learning tools like Assemblr Edu to enrich moral education, while emphasizing the importance of institutional readiness to maximize their educational impact. These findings contribute to the broader discourse on the integration of Information and Communication Technology (ICT) in moral and character education in the context of international schools.